Go to your tomb--right now! - R. L. Stine; Stine, R. L. (New York : Pocket Books, 1997)
After Jack's friend dares him to kiss the stone statue in the cemetery, a young girl appears and tells them she can grant their wish if they will help her travel back in time, but Jack wonders if having his wish come true is worth it.
"A Minstrel book."
"A Parachute Press book."
3.5.
3.5
3-6
Keywords: Ghosts -- Fiction; Horror stories; Time travel -- Fiction; Ghost stories; Horror fiction; Space and time -- Fiction